EFFECT OF MULTIPLE WASHING ON THE OPTICAL AND SHIELDING PROPERTIES OF COTTON FABRICS - ТРУБА, А. А.; СВИДЛО, О. С.; АРАБУЛІ, С. І.; АРАБУЛІ, А. Т.; КОВТОНЮК, Л. М. (Technologies and Engineering, 2025)
Purpose. Cotton fabrics are most often used for the production of summer clothing. Such fabrics should provide aesthetic performance, high wearing comfort and protection from the negative effects of ultraviolet (UV) radiation. At the same time, products made from these fabrics are subject to frequent washing, which can negatively affect the appearance of the clothing and the shielding properties of the fabrics. Methodology. Theoretical and experimental studies are based on the basic principles of textile materials science. The optical properties of fabrics were evaluated in the Commission Internationale de l’Eclairege L*a*b* (CIELab) color space using a 3NH NR-20XE colorimeter at D-65/10 radiation. The ability of fabrics to shield UV radiation was evaluated by the values of the transmittance (%) on a DU-8800D UV-Vis spectrophotometer (Drawell International Technology Ltd) in accordance with the EN 13758-1:2002 standard with the determination of the ultraviolet protection factor (UPF). Results. Modern measures for protecting humans from UV radiation were analyzed. It has been established that clothing is considered one of the most effective means of protecting human skin from UV, while the shielding properties of textiles are decisive. The influence of the main indicators of textiles (chemical composition of fibers, porosity and color) on the level of protection of 8 investigated fabrics against UV radiation was studied. The effect of repeated washing on the optical and shielding properties of cotton fabrics was studied. Scientific novelty. It has been experimentally proven that multiple washing of cotton fabrics leads to visible changes in the optical and structural properties of the fabrics. It has been established that the most informative parameter for establishing the effect of "washing cycles" on optical (color) and screening properties is the parameter L* – lightness. The obtained data confirm the hypothesis that a decrease in the value of the parameter L* leads to a decrease in the value of the UV radiation transmittance (the correlation coefficient is 0.9).Practical value. The influence of structural and optical properties of textile materials on their ability to shield UV radiation is summarized. Dependencies between the optical and shielding properties of cotton fabrics based on the results of multiple washings are established.